Induced P_3-Packing k-partition Number for Certain Graphs - Xavier, Antony; Theresal, Santiagu; Raja, S. Maria Jesu Raja (International Journal of Computer Sciences and Engineering, 2025)
Finding a partition V_1,V_2,...,V_k of V(G) with minimum k is called the induced H-packing k-partition problem of G. The minimum induced H-packing k-partition number is denoted by ipp(G,H). In this paper we determine an induced P_3-packing k-partition number for Butterfly Networks, Honeycomb Networks, and Circum Pyrene with H is isomorphic to P_3.